Disease and Ethiopian wolves (Canis simensis): trialling the feasibility of oral vaccination against rabies - Gordon, C; Christopher H Gordon (2013)
Disease often plays a large role in the population dynamics of wild canids, and is the most immediate threat to the Endangered Ethiopian wolf (Canis simensis). Well-documented rabies epizootics have devastated the Bale wolf population three times since 1991, with mortality of 65-75% in affected areas. Intensive monitoring permitted the diagnoses of wolf carcasses found in 2008/09, which confirmed two separate introductions of the same rabies strain from the sympatric dog reservoir, with severe consequences for the affected populations. During emergency interventions, 98 wolves were vaccinated in 20 packs adjacent to affected packs, to contain the spread of rabies, as in 2003. The impact of rabies upon Ethiopian wolves may be compounded by canine distemper virus (CDV). The first recorded CDV mortalities showed high mortality rates of 43-68% during two separate epizootics in 2005/06 and 2010. Mortality was higher in sub-adults (83-87%) than adults (34-39%), and breeding success immediately after an epizootic was unusually low. In the Web Valley, CDV in 2010 followed the rabies outbreak two years prior, affecting a wolf population that had not fully recovered, and four of seven packs disappeared. The combined impact of rabies and CDV at low inter-epizootic intervals markedly affected Ethiopian wolf pack persistence and population recovery, as was predicted by previous models. The severe effect of recurrent epizootics on wolf population dynamics, combined with the fragility of small population sizes, highlight the need to improve current disease control policies. To date, efforts to protect wolves have focused on vaccination of the dog reservoir, and the emergency vaccination of wolves in response to rabies outbreaks. Oral vaccination potentially offers an efficient and economical method to inoculate both dogs and wolves against rabies, and was identified as a key tool for wolf conservation. To test its suitability, field trials of the oral vaccine Rabigen® SAG2Dog were conducted on dogs. In total, 142 vaccines were delivered to 116 dogs using a variety of baits. Intestine baits had highest uptake rates but meat baits were chewed the longest, maximising the potential for vaccine absorption. Rabies antibody titres in pre- and post-vaccination samples were assessed using the FAVN test at a 0.5IU/ml protection threshold. The number of dogs to seroconvert following vaccination was low (11%), even at a reduced threshold of 0.2IU/ml (37%). There were limited anamnestic responses to the vaccine (an enhanced reaction in previously exposed dogs) in baseline positive dogs (25%). Low sero-conversion and logistical difficulties of maintaining a cold chain for this vaccine, offer little evidence that Rabigen® SAG2Dog would provide effective rabies protection for dogs. Bait uptake and the effectiveness of Rabigen® SAG2Dog were also tested on wolves. Meat baits had highest uptake (50-53%), and targeted delivery had better uptake than random delivery. Subsequently, Rabigen® SAG2Dog was delivered using the favoured meat bait and targeted delivery to one wolf pack. Oral vaccine baits were consumed by five of eight wolves, and blood samples were drawn from four of these wolves and one control two weeks later. Two of the four wolves that ate baits had positive rabies titres (>0.5 IU/ml), while a third had raised levels. All wolves from the pack are alive 18 months after delivery. This small, controlled trial confirms the potential for Rabigen® SAG2Dog to provide rabies protection to Ethiopian wolves. Further extended trials will be required before oral rabies vaccination can be implemented as a proactive disease management approach.